"Antisocial socialization" as a source of society's systematic moral deviation - Zelinskiy, М.; Nevidoma, Y. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article considers with the problems of human existence at different levels of socialization. The authors emphasize the need to improve the spiritual and moral foundations of society development, as a guarantee of successful social and economic transformations in the country.
Keywords: socialization; moral and spiritual development; condition of modern society; social change; deviation